Scarf Osteotomy in Treating Hallux Valgus: Clinical and Radiographical Outcome and Technical Notes - Kin-Wing Law (Journal of Orthopaedics, Trauma and Rehabilitation, 2014)
Introduction: Scarf osteotomy can be a technically demanding procedure and early reports have shown high complication rates. Proponents, however, suggest that this type of osteotomy is versatile and allows for both translation and angulation correction of the hallux valgus (HV) deformity. The purpose of this study was to evaluate the clinical and radiological results of the scarf osteotomy procedure performed in our hospital. Materials and methods: We retrospectively reviewed 31 feet in 25 patients with an average follow-up duration of 16 months (range: 6–30 months). Results: On the latest follow up, 77% of the patients were satisfied with the result, with an average postoperative American Orthopaedic Foot and Ankle Society score of 88. The average improvement of HV angle was from 37.9° to 10.0°. The intermetatarsal angle improved from 16.0° to 8.0°. The average first metatarsal shortening was 0.3 mm. Neither delayed union nor osteonecrosis was observed. Conclusion: Scarf osteotomy is a reliable procedure to achieve correction of HV deformity with good patient satisfaction.